Development of Pests and Diseases Booklet Crystal Guava (Psidium guajava L.) based on Line from Identification Results in Helena Guava Garden, Candi Village, Jatirejo, Karanganyar as A Guide to Crystal Guava Cultivation - Hanik, Nur Rokhimah; Wiharti, Tri; Rosyid, Ahmad; Eskundari, Ratna Dewi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
A booklet is a combination of a leaflet and a small book so it is practical and can be used as a guide. The aim of the research is to develop a booklet on pests and diseases of crystal guava as well as online-based management methods. Pest and disease booklets need to be developed considering that pests and diseases are the main obstacles to agricultural productivity, disrupting plant physiology and growth so that they can reduce crop yields. Data collection was carried out through observing samples of crystal guava plants, as well as interviews with owners and managers to obtain information about pests and diseases of crystal guava. Data was analyzed descriptively qualitatively. The results of the research found 4 crystal guava pests, namely: codot (Cynopterus spp.), ladybugs (Epilachna admirabilis), fruit flies (Bactrocera dorsalis), and mealybugs (Paracoccus marginatus). The diseases found were the fungus Capnodium citri (sooty dew), algae (Chephaleuros virescens), fungus (Festlotiopsis psidii), and nutrient deficiencies (potassium/magnesium). Crystal guava is cared for by keeping the garden clean, spacing the plants, applying fertilizer, spraying insecticide, installing fruit fly traps, and wrapping the young fruit. The research output is in the form of a booklet, then converted into a video and uploaded to YouTube at the link: https://youtu.be/9bzldxynnl3q. This research still needs to be carried out in two seasons, namely dry and rainy, so that it can produce more types of pests and diseases, so that the online booklet results are more optimal.